Rancang Bangun Aplikasi Tata Kelola Teknologi Informasi (TI) Berbasis Framework COBIT 5 menggunakan metode prototype Dengan Studi Kasus Universitas ABC Surabaya - Akhlaqul Wong Karimatullah Margin Wilujeng; Adib Pakarbudi (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2023)
In today's digital era, the use of information technology (IT) is becoming increasingly important for various organizations, including those in the education sector. However, the use of IT that is not managed properly can cause various risks and negative impacts, such as vulnerabilities to information security and poor IT performance. Therefore, IT governance is becoming increasingly important as an effort to ensure the effective and efficient use of IT. IT based on the COBIT (Control Objectives for Information and Related Technology) framework uses the prototype method in a case study at ABC University Surabaya. The COBIT framework is used as a guide in managing IT resources with a focus on business objectives and risk management. The prototype method is used as a software development method that allows users to test and provide input on prototypes before the final product is made.